2022
DOI: 10.33395/sinkron.v7i4.11815
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Motorcycle Theft Prevention System Based on Arduino Uno

Abstract: The high rate of motorcycle theft was reportedly caused by the negligence of the owner of the motorcycle itself, including forgetting to double lock and leave the key on the motorcycle. This research offers a new approach to prevent motorcycle theft by designing an automatic double lock system through ignition keys, buzzer reminders for left keys, and coordinator points using GPS to track the position of a motorcycle. Automatic dual locks are designed using a solenoid that locks the front and rear disc brakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the proposed system the position of the motorcycle could be tracked by using GPS coordinates which was provided by GPS Ublox neo 6M component different from research reported in [17][18] which used GPRS Shield SIM808. GPS Ublox neo module is a popular component for various position tracking application development such as reported in [19][20]. In order to obtain location coordinates from the GPS Ublox Neo 6M, this component needs to be connected to the internet so that the coordinate could be monitored by using the Blynk platform on a smartphone online.…”
Section: Block Diagram Of the Systemmentioning
confidence: 99%
“…In the proposed system the position of the motorcycle could be tracked by using GPS coordinates which was provided by GPS Ublox neo 6M component different from research reported in [17][18] which used GPRS Shield SIM808. GPS Ublox neo module is a popular component for various position tracking application development such as reported in [19][20]. In order to obtain location coordinates from the GPS Ublox Neo 6M, this component needs to be connected to the internet so that the coordinate could be monitored by using the Blynk platform on a smartphone online.…”
Section: Block Diagram Of the Systemmentioning
confidence: 99%